Prevalence of latent tuberculosis infection and its associated factors among patients with diabetes in Hospital Universti Sains Malaysia - Ai Ping, Phan (2015)
Introduction: The important association between tuberculosis and diabetes mellitus is even more prominent in developing countries, including Malaysia, where tuberculosis is endemic and the burden of diabetes mellitus is fast increasing. Objectives: To determine the prevalence of latent tuberculosis infection among patients with diabetes and factors associated with it. Methodology: A cross sectional study was conducted from October 2013 to January 2015. Mantoux test was performed on the patients whom are eligible and gave consent to participate in the study and reading was carried out at 72 hours. Respondents with mantoux reading of 10mm or more with a normal chest radiograph were diagnosed with LTBI. Results: The response rate for this study was 93.7% with 319 respondents tested with tuberculin skin test for latent tuberculosis infection. The prevalence of latent tuberculosis infection among diabetic patients was 11.4%. Education level was significant associated with LTBI; while other factors studied (age, gender, duration of diabetes, HbA1c result, smoking status, presence of any co-morbities and on insulin treatment) showed no significant association with latent tuberculosis infection in diabetic patients